Development of Art Activities to Promote Appreciation Values of Southern Handicraft Identity for Youth - Pruek-Udom , Theeti; Boonyananta, Soamshine (Journal of Education Studies, Chulalongkorn University, 2020)
The objectives of this research are (1) to analyze the Identity pattern of southern handicraft and (2) to develop a series of artistic activities to promote the identity of southern handicraft. The target group are youths aged 15-25 in Songkhla province. The research instruments consisted of 2 sets. The first set was to collect information on the values and identities of Southern handicraft and to develop art activities from that information. The first set consists of 3 parts, 1) interviewing best practice activity experts 2) interviewing Southern handicraft experts 3) complete an activity report based on the good practice observations. The second set of research instruments was to assess the quality of the art activity developed. The second set consists of 4 parts 1) Appreciation assessment 2) Participant interview form 3) Post-assessment on the satisfaction 4) Holistic behavioral assessment. The data was then analyzed using descriptive statistics. The findings revealed that natural materials are available in the southern region and the colors used are particularly bright with decorated patterns inspired by the local nature. A series of activities consists of 6 parts: (1) making brooch from Thai Nang Talung, (2) Making Pah Yok Meung Na-Korn from paper, (3) designing and making patterns on Sa-Ting Moh pottery, (4) Making Beramas pattern on notebook, (5) Making ring by Na-Korn Niello Wares technique, and (6) Design pen pattern by Lygodium. The results of the development trial found that after the youth activity, the average value of the identity in the arts and crafts of the south was higher (M = 51.93) than before the activity (M = 41.37) at the statistical significance of .05.